2019
DOI: 10.1096/fj.201801921r
|View full text |Cite
|
Sign up to set email alerts
|

High glucose–induced ubiquitination of G6PD leads to the injury of podocytes

Abstract: Oxidative stress contributes substantially to podocyte injury, which plays an important role in the development of diabetic kidney disease. The mechanism of hyperglycemia‐induced oxidative stress in podocytes is not fully understood. Glucose‐6‐phosphate dehydrogenase (G6PD) is critical in maintaining NADPH, which is an important cofactor for the antioxidant system. Here, we hypothesized that high glucose induced ubiquitination and degradation of G6PD, which injured podocytes by reactive oxygen species (ROS) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…ACHN and 786-O cells were pretreated with or without 6-AN for 4 h and subsequently stimulated with caffeine for 48 h. As expected, inhibition of G6PDH with 6-AN abrogated the inhibitory effects of caffeine on RCC cell viability ( Figures 4A,B ). Previous studies have shown that lipids such as PA could significantly reduce the protein expression of G6PDH, which results in similar results with G6PDH knockdown ( Wang et al, 2019 ; Yang et al, 2019 ). The inhibitory effect of PA on G6PDH expression in ACHN and 786-O cells was confirmed by western blotting analysis ( Figures 4C,D ).…”
Section: Resultssupporting
confidence: 67%
“…ACHN and 786-O cells were pretreated with or without 6-AN for 4 h and subsequently stimulated with caffeine for 48 h. As expected, inhibition of G6PDH with 6-AN abrogated the inhibitory effects of caffeine on RCC cell viability ( Figures 4A,B ). Previous studies have shown that lipids such as PA could significantly reduce the protein expression of G6PDH, which results in similar results with G6PDH knockdown ( Wang et al, 2019 ; Yang et al, 2019 ). The inhibitory effect of PA on G6PDH expression in ACHN and 786-O cells was confirmed by western blotting analysis ( Figures 4C,D ).…”
Section: Resultssupporting
confidence: 67%
“…Given the unchanged G6PDH activity levels in the crude insect homogenates and the constant V max calculated from the purified enzyme samples, it seems likely that the reduction in ubiquitin levels may be necessary to maintain levels of G6PDH during the winter months to help the animal cope with repeat freeze‐thaw cycles. Interestingly, ubiquitin is known to mediate G6PDH expression levels in the human kidney where elevated levels of glucose result in an increase in G6PDH ubiquitination resulting in a depletion of this enzyme and subsequent oxidative stress due to decreased NADPH pools (Wang et al, ). The results here raise additional questions regarding whether this decrease in ubiquitin levels is unique to this enzyme or if a reduction in ubiquitin ligation is a feature common to many proteins in E. solidaginis as an over‐wintering response.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD) catalyzes the oxidative pentose phosphate pathway, an essential process producing ribose-5-phosphate and NAPDH from G6P. G6PD was observed to be ubiquitinated and degraded by VHL E3 ubiquitin ligase in podocytes [272]. VHL is tumor-suppressor protein [273].…”
Section: Ubiquitination and Metabolic Enzymesmentioning
confidence: 99%